2004
DOI: 10.1097/01.prs.0000142474.25114.cb
|View full text |Cite
|
Sign up to set email alerts
|

Coronal Ring Involvement in Patients Treated for Unilateral Coronal Craniosynostosis

Abstract: The etiopathology of the clinical entity normally referred to as unilateral coronal synostosis is commonly used to connote unilateral fusion of the frontoparietal suture. However, other sutures in the coronal ring may exhibit synostosis concomitant with or independent from frontoparietal synostosis and give rise to similar clinical phenotypes. This study retrospectively analyzes high-resolution computed tomographic data sets to determine patency of sutures within the coronal ring. Computed tomographic scan dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 9 publications
0
22
0
Order By: Relevance
“…These physical findings are consistent with other cases. 4,7,8,11 Dundulis et al reported a case of IFS with the above-noted findings but with chin point deviation to the affected side 5 ( Table 1). The clinical diagnosis of IFS can be challenging since this entity has physical findings of both DP and the more common hemicoronal ring fusion, UCS.…”
Section: Discussionmentioning
confidence: 99%
“…These physical findings are consistent with other cases. 4,7,8,11 Dundulis et al reported a case of IFS with the above-noted findings but with chin point deviation to the affected side 5 ( Table 1). The clinical diagnosis of IFS can be challenging since this entity has physical findings of both DP and the more common hemicoronal ring fusion, UCS.…”
Section: Discussionmentioning
confidence: 99%
“…The typical harlequin deformity described in coronal synostosis, with verticalization of the orbit, is usually not seen and has not been diagnosed in our series. According to Dundulis et al [10], this deformity might be related with a compensatory growth at the patent frontosphenoidal suture in case of coronal synostosis, as the distortion is lessened when there is a complete coronal and frontosphenoidal synostosis. This may explain the absence of harlequin's eye in isolated frontosphenoidal synostosis.…”
Section: Discussionmentioning
confidence: 99%
“…Isolated frontosphenoidal synostosis, with a patent coronal suture, would have a different starting point and has been described in few cases [10,11,16]. Its recognition is important to assure the child a proper treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anterior plagiocephaly is the second most frequent type of nonsyndromic craniosynostosis [1,2,3]. It is described as a unilateral flattening of the forehead which is mostly secondary to unilateral coronal suture synostosis, but in some rare instances other sutures may be involved with specific clinical and radiological features.…”
Section: Introductionmentioning
confidence: 99%